Basic concepts of environmental chemistry - Connell, Des W. (London, 2005)
Incorporating advances made since the 1997 publication of the first edition, this book includes material on toxic metals, atmospheric pollution, radionuclides, acid drainage water, and risk assessment. It addresses topics such as polarity, partition behavior, fugacity, and solubility as well as the basic chemistry of compounds and processes in the environment. The author begins with coverage of the basic properties of chemicals in terms of polarity, water solubility, and vapor pressure, followed by chapters on environmental transformations and toxicity. Expanding on these fundamentals, he describes contaminants in the environment and pollution processes in the air, water and soil environments
Keywords: Environmental chemistry